Comparison of SSVEP BCI and eye tracking for controlling a humanoid robot in a social environment - Kishore, Sameer; Gonzalez Franco, Mar; Hintemüller, Christoph; Kapeller, Christoph; Guger, Christoph; Slater, Mel; Blom, Kristopher J (PRESENCE: Teleoperators and Virtual Environments, 2014)
Recent advances in humanoid robot technologies have made it possible to inhabit a humanlike form located at a remote place. This allows the participant to interact with others in that space and experience the illusion that the participant is actually present in the remote space. Moreover, with these humanlike forms, it may be possible to induce a full-body ownership illusion, where the robot body is perceived to be one's own. We show that it is possible to induce the full-body ownership illusion over a remote robotic body with a highly robotic appearance. Additionally, our results indicate that even with nonmanual control of a remote robotic body, it is possible to induce feelings of agency and illusions of body ownership. Two established control methods, an SSVEP-based BCI and eye tracking, were tested as a means of controlling the robot's gesturing. Our experience and the results indicate that both methods are tractable for immersive control of a humanoid robot in a social telepresence setting.